EDUKASI FUNGSI KEMASAN UNTUK PRODUK KULINER PENGUSAHA UMKM DI KECAMATAN BANYUMANIK SEMARANG - Bayu Widiantoro; Louis Cahyo Kumolo Buntaran (JUARA: Jurnal Wahana Abdimas Sejahtera, 2021)
The complaint from MSME entrepreneurs, especially residents of Banyumanik District, Semarang City, is that customers do not increase even though they have a culinary business for quite a long time. The sale of these culinary products only uses plain plastic or cardboard packaging, which makes the product not interesting customers. The purpose of this community service is to provide awareness to the public regarding the function of packaging which is currently developing not only as a protector of their products, but also as a medium for advertising and promoting its products to potential consumers. This activity provides training to MSME entrepreneurs on how to provide various information needed as well as colors and dimensions on product packaging so that it becomes something interesting. The results of the training carried out received a positive response from the participants to apply it in the sale of culinary products. In addition, MSME entrepreneurs hope that there will be further training on branding and the application of typography in packaging